2014
DOI: 10.5507/bp.2013.038
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma and CNS. Comparison of fMRI results in high tension and normal tension glaucoma

Abstract: Aim. The objective of our work was to determine whether there is a difference in fMRI activation between patients with high tension glaucoma (HTG) and those with normal tension glaucoma (NTG). Method. The sample consisted of eight patients with different stages of high tension glaucoma (3 females aged 41-65 and 5 males aged 40-73 years) and eight patients, also with different stages of normal tension glaucoma (6 females aged 53-70 and 2 males aged 40-52 years). The control group consisted of eight healthy subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
0
11
0
7
Order By: Relevance
“…Few fMRI studies have been conducted on glaucoma patients. [ 21 23 , 32 34 ] The first such work, comparing VF defects with fMRI responses, included seven patients with various forms of optic neuropathy, including glaucoma. It was found that stimulation of the affected eye did not activate the primary visual cortex in the region corresponding to the VF defect [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few fMRI studies have been conducted on glaucoma patients. [ 21 23 , 32 34 ] The first such work, comparing VF defects with fMRI responses, included seven patients with various forms of optic neuropathy, including glaucoma. It was found that stimulation of the affected eye did not activate the primary visual cortex in the region corresponding to the VF defect [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional activity resulted greatly reduced within primary visual cortex after visual input from the glaucomatous eye in all studies using fMRI both in POAG (Duncan et al, 2007a ; Qing et al, 2010 ; El-Rafei et al, 2013 ; Lestak et al, 2014 ; Borges et al, 2015 ; Gerente et al, 2015 ; Murphy et al, 2016 ; Zhang et al, 2016 ; Jiang et al, 2017 ; Zhou et al, 2017b ), NTG (El-Rafei et al, 2013 ; Lestak et al, 2014 ; Zhang et al, 2016 ) and PACG patients (Song et al, 2012 ).…”
Section: Resultsmentioning
confidence: 94%
“…The frontal lobe also transmits visual information to the oculomotor complex [16] . Some prior studies had similar results, although none of these studies analyzed different types of primary glaucoma simultaneously [25,26] . Moreover, in our study, when we used BA18 and BA19 (related to superior visual cortex) as the seeds, we found that the connection between the frontal lobe and the occipital lobe significantly increased in all three groups of visual field-defected glaucoma patients, which indicated that the frontal lobe may have a special relationship with the visual pathway.…”
Section: Brain Region Of Functional Connectivitymentioning
confidence: 97%